DESIGN OF RADIUS SERVER ON SERVER NETWORK INTERNET FACULTY OF COMPUTER SCIENCE UNIVERSITY MUHAMMADIYAH METRO - Arif Hidayat (STMIK Pringsewu Lampung, 2018)
The destination process or otherwise known as routing. Mikrotik Router has provided the management system to hotspot user through separate program package named User Manager. The main problem is the integration of user manager applications into the hardware router Mikrotik considered less effective and flexible because to perform the process of management of the user hotspots must be done on each router located in the hotspot area which will certainly take a relatively long time. From these problems, then created a new system by utilizing external PCRADIUS server as the center of the process of authentication and management of users Mikrotik hotspot. The purpose of this research is to design radius server on internet server network Faculty of Computer Science University Muhammadiyah Metro. While the final results of this study are implementing radius on the Internet network server Faculty of Computer Science (FIKOM) Universitas Muhammadiyah Metro.